Spectrum of Clinico-Pathological Profile of Poems Syndrome: An Extensive Analysis on Laboratory Interpretations - Vaithy, Anandraj; K, Shanmugasamy; ., Bhavani; G, Koteeswaran (Annals of Pathology and Laboratory Medicine, 2018)
Background: Plasma cell Dyscrasias being an unique hematological neoplasm characterized by monoclonal B cell proliferation of Plasma cell, it is usually associated with paraneoplastic syndromes having many differentials. Among the types, POEMS syndrome is an unusual condition characterized by spectrum of clinical manifestations involving hematopoietic and systemic manifestation with many co-morbidities. Laboratory diagnosis remains as the mainstay of diagnosis often making the clinician to examine retrospectively. Among various laboratory tests, Hematological parameters allied with biochemical values and radio-imaging are contributory. In the present study we analyzed the spectrum of Clinical manifestations of POEMS syndrome and emphasized the fact that clinico-pathological correlation helps in early diagnosis of POEMS syndrome, thereby prompt treatment can be initiated. Methodology: Specific criteria was fixed to label POEMS syndrome based on the knowledge gained by previous Research works. A clear clinical details was collected from the patients in a prescribed proforma. Among the studied cases the criteria to label POEMS syndrome included the following clinical manifestations and its subsequent laboratory interpretations Polyneuropathy, M-protein, Organomegaly (hepatomegaly, splenomegaly or lymphadenopathy), Endocrinopathy (hypothyroidism, diabetes mellitus, hypoadrenocorticismorhypogonadism), skin changes (hyperpigmentation, hypertrichosis, or thickening), and Effusion or Peripheral edema. Three of these above six criteria were kept as minimal requirement for the diagnosis. While the first two were kept as major criteria, the rest are assumed to be minor criteria. Results:The study period was for a period of seven years and included a series of 9cases.Male preponderance was noted with high incidence in middle age. At many instances it was evident that laboratory diagnosis especially hematological parameters reinforced retrospective evaluation by Clinician to clinch the diagnosis. While M- band electrophoresis and high ESR was uniformly seen in all cases, the associated co-morbidities are variable with skin lesions and bone marrow plasmacytosis. Biochemical & radiological reports were contributory in picking up the condition. Conclusion: POEMS syndrome is a paraneoplastic condition affecting the middle age individuals with male preponderance unlike other classical myeloma. The present study showed that incidence of POEMS syndrome is fairly higher and judicious correlation of laboratory interpretations especially hematological parameters will definitely aid in better health care management of the patients.